Entacapone: improving aqueous solubility, diffusion permeability, and cocrystal stability with theophylline - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Suresh, Kuthuru; Gunnam, Anilkumar; Nangia, Ashwini (Crystal Growth & Design, 2018)
Cocrystallization is a well-established technique to improve the solubility, bioavailability, and stability of active pharmaceutical ingredients (APIs) but permeability and diffusion rate control via cocrystals is relatively less well studied, and the exact role of coformers in influencing the diffusion rate of drug cocrystals is still not fully understood. The aqueous solubility and permeability diffusion of Entacapone, ETP, a Biopharmaceutical Classification System (BCS) Class IV drug of low solubility and low permeability, with Generally Regarded as Safe (GRAS) coformers has been studied. Fixed stoichiometry cocrystals of ETP with acetamide (ACT, 1:1), nicotinamide (NAM, 1:1), isonicotinamide (INAM, 1:1), pyrazinamide (PYZ, 1:1), and isoniazid (INZ), 1:1) were prepared by solvent-assisted grinding. Theophylline (THP) resulted in a cocrystal hydrate (ETP-THP-FIYD 1:1:1). The cocrystals were structurally characterized by single crystal and powder X-ray diffraction, DSC and TGA thermal measurements, and IR and NMR spectroscopy. Solubility and dissolution rate showed that there is a correlation between cocrystal stability and solubility governed by the heteromeric N-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O hydrogen bonds and conformational changes of ETP in cocrystal structures. ETP-THP-HYD and ETP-PYZ exhibit faster dissolution rate and high solubility and they are stable in phosphate buffer medium compared to the other cocrystals which dissociate partially during solubility experiments. Diffusion rates in a Franz cell showed that the stable and high solubility ETP-THP-HYD cocrystal has good permeability. Given that stability, solubility, and permeability are in general inversely correlated, the entacapone-theophylline hydrate cocrystal is a unique example of the thermodynamically stable cocrystal exhibiting high solubility and high permeability.

Electron crystallography - Blake, Alexander J.; de Boissieu, Marc; Nangia, Ashwini (IUCRJ, 2019)